Early Christianity in Rome: literary, historical, and archaeological traditions - Schröter, Jens (Zeitschrift für die neutestamentliche Wissenschaft und die Kunde der älteren Kirche, 2026)
The volume explores the beginnings of Christianity in Rome, the political and religious center of the Roman empire. Early Christian writings such as Paul’s letters to the Romans, the Acts of the Apostles, First Clement and the Shepherd of Hermas demonstrate that Rome became an important place for early Christians by the end of the first/beginning of the second century. In this period, one can also detect a early separation of Jewish and Christian communities in Rome. In the second century, several prominent philosophical teachers came to Rome and taught the Christian message from their respective viewpoints. To these belong Marcion, Valentinus, Justin Martyr and Tatian. The diverse interpretations of the Christian message resulted in the formation of different communities, e.g. the Marcionites, the Valentinians and the "main church" to which apparently Justin belonged. The book also examines the archaeological remains of the early Christians. Although the evidence is sparse, some things can be said about the burial places of Peter and Paul and about the so-called "house churches" of early Christians. Taken together, the articles in this volume will advance the discussion about Christianity in Rome in the first three centuries
"This volume goes back to a conference entitled 'Early Christianity in Rome', which took place from April 18 to 20, 2024, at the Pontificio Istituto Biblico in Rome." - Preface
Keywords: Konferenzschrift -- 2024 -- Rom; Urchristentum; Römisches Reich